A reconciliation study of different resource estimation methods and drill hole spacing as applied to the Langer Heinrich calcrete-hosted uranium deposit, Namibia - Baufeldt, Sven (Rhodes University, Faculty of Science, Department of Geology, 2018)
The Langer Heinrich calcrete hosted uranium deposit is situated approximately 90 km to east of the coastal town of Swakopmund in Namibia. It is run by an Australian owned company, Paladin Energy Limited, along with China National Nuclear Corporation (CNNC) who maintain 25% of the shares. Production commenced in 2007 and has been ongoing. Carnotite is the primary and only ore mineral, and the nature of mineralisation within the Langer Heinrich palaeo channel dictates westward-directed continuous open pit mining. Smaller-scale 1micro pits target near-surface, high-grade, lenses toward the east. The high variability in uranium grade over relatively short distances complicates the grade estimation process. This combined with a low uranium price, and a study aimed at optimising of mine production is one of the key drivers for the research presented in this thesis. The efficacy of four resource estimation techniques, commonly used in the mining industry, are investigated by application to variable exploration, infill drilling and grade-control drill pattern spacing. The drill spacing includes regular grids of 50 m x 50 m, 25 m x 25 m and 12,5 m x 12,5 m exploration data. Also included is grade control drill data, drilled on a 4 m x 4 m spacing. The current selective mining unit (SMU) is 4mE x 4mN x 3mRl which is an indication of the minimum dimension whereby the loading equipment can separate ore from waste. The two datasets are processed by four estimation techniques: Inverse Distance Weighting (IDW, squared and cubed), Ordinary Kriging (OK), Multiple Indicator Kriging (MIK) and Conditional Simulation (CS). The two datasets consisted of real-time mining data from pit G1 (micro-pit) in the eastern parts of the mining licence, and pit H1 (continuous larger open pit) in the western area of the palaeo channel. The reconciliation project aims to provide results suitable for devising optimised mining strategies, particularly in future targets where drill spacing can perhaps be improved to provide suitable data with a greater cost saving strategy. Along with the optimal drill spacing or combination thereof, a preferred estimation technique can be suggested and recommended for future operations that involve mining of surficial calcrete-hosted uranium deposits. Results of this study show that 12,5 m x 12,5 m drill spacing provided estimation accuracies similar to that of the narrow 4 m x 4 m grade control spacing (blast hole drilling spacing). The 12,5 m x 12,5m spacing has potential for accurate grade estimations during mining, and could be supplemented by infill downhole radiometric logging on a 4 m x 4 m spacing when 1 Micro pit: Small pits within palaeo channel usually targeted for their near surface high-grade ore necessary. In general, Multiple Indicator Kriging (MIK) provided the most accurate and robust estimations on the wider spaced exploration data and conditional simulation (CS) proved more efficient on the narrow grade control data. These results correspond with current exploration practices for surficial uranium deposits world-wide. Deposit type, therefore complexity and hence SMU sizes play a pivotal role in drill hole planning and estimation accuracies.
Keywords: Uranium -- Namibia; Calcretes -- Namibia; Carnotite -- Namibia; Uranium mines and mining -- Namibia; Uranium ores -- Geology -- Namibia; Langer-Heinrich Uranium mine